Organ Cultures for Retinal Diseases - Hurst, José; Fietz, Agnes; Tsai, Teresa; Joachim, Stephanie C.; Schnichels, Sven (Frontiers in Neuroscience, 2020)
The successful development of novel therapies is closely linked with understanding the underlying pathomechanisms of a disease. To do so, model systems that reflect human diseases and allow for the evaluation of new therapeutic approaches are needed. Yet, preclinical animal studies often have limited success in predicting human physiology, pathology, and therapeutic responses. Moreover, animal testing is facing increasing ethical and bureaucratic hurdles, while human cell cultures are limited in their ability to represent in vivo situations due to the lack of the tissue microenvironment, which may alter cellular responses. To overcome these struggles, organ cultures, especially those of complex organs such as the retina, can be used to study physiological reactions to substances or stressors. Human and animal organ cultures are now well established and recognized. This mini-review discusses how retinal organ cultures can be used to preserve tissue architecture more realistically and therefore better represent disease-related changes. It also shows how molecular biological, biochemical, and histological techniques can be combined to investigate how anatomical localization may alter cellular responses. Examples for the use of retinal organ cultures, including models to study age-related macular degeneration (AMD), retinitis pigmentosa (RP), central artery occlusion (CRAO), and glaucoma are presented, and their advantages and disadvantages are discussed. We conclude that organ cultures significantly improve our understanding of complex retinal diseases and may advance treatment testing without the need for animal testing.